Systems Thinking for School Leaders. Holistic Leadership for Excellence in Education - Shaked, Haim; Schechter, Chen (Springer, 2017)
This book presents a new approach to school leadership - Holistic School Leadership, whereby school leaders lead schools through systems-thinking concepts and procedures. Facing growing complexity, change and diversity, school leaders need to regularly apply the systems view and perform at the systems level. This book proposes a holistic approach, providing school leaders with systemic principles of action for excellence in education. "What a wonderful book - once I started it, I couldn't put it down. The book masterfully makes a systems leadership perspective accessible and grounded in the reality of the daily life of educators. Holistic School Leadership is a "must read" for anyone who has the responsibility for making schools better places, from professors to emerging teacher leaders."Karen Seashore (Louis), Regents Professor of Organizational Leadership, Policy and Development, University of Minnesota "Shaked and Schechter have constructed a much needed bridge to the future of educational leadership, a future of systemic thinking and positivity." Joseph Murphy, Professor of Education and Public Policy, Peabody College of Education, Vanderbilt University "Shaked and Schechter offer a comprehensive yet concise account of the meaning of systems thinking. The authors systematically develop their Holistic School Leadership approach with compelling examples, carefully attending to the perennial challenge of implementation. Important reading for scholars and practitioners of school leadership and management!"James P. Spillane, Olin Professor in Learning and Organizational Change, Northwestern University "This is the most important book on systems thinking since Senge's (1990) seminal work on learning organizations. Shaked and Schechter demonstrate the critical and practical utility of systems thinking for school leaders--a must read for all reflective practitioners." Wayne K. Hoy, Professor Emeritus, The Ohio State University